Integration in euro area retail banking markets: convergence of credit interest rates - Laura Vajanne (Bank of Finland, 2007)
Since the introduction of the single currency in 1999, major progress has been made towards achieving an integrated European capital and financial market. Available evidence suggests, nevertheless, that the degree of integration varies greatly depending on market segment. Retail banking markets are generally seen to be much less integrated than other segments of financial markets. Most consumers still buy retail financial services from domestic suppliers, cross-border entry of financial services firms is rare even if it is growing and the range of products available or terms attached thereto differ substantially across euro area countries. The purpose of this paper is to assess integration of retail banking in the euro area from January 2003 to December 2006. The empirical analysis is based on a monthly panel of recently published harmonised interest rates from euro area monetary financial institutions. We estimate two commonly used measures of convergence, namely ?- and ?-convergence, to assess the speed and degree of integration. Tests for convergence are based on a panel unit root test. The tests provide evidence of a process of convergence in retail banking credit interest rates for households and non-financial corporations and show this convergence has recently being continuing. Thus, even if there are substantial cross-country differences in interest rate levels, progress towards integration is observable.
URN:NBN:fi:bof-20140807388
Keywords: F36; G21; 330; financial market integration; euro area interest rates; panel data estimation